2019
DOI: 10.15448/1980-8623.2019.3.31349
|View full text |Cite
|
Sign up to set email alerts
|

Revisão sistemática sobre fatores associados à relação entre habilidades sociais e suporte social

Abstract: Um repertório bem desenvolvido de habilidades sociais permite interações sociais de melhor qualidade. Assim, habilidades sociais afetam o acesso a suporte social, mas pouco se sabe sobre fatores que aumentam ou reduzem a eficácia das habilidades sociais na obtenção desse tipo de suporte. O objetivo deste estudo foi identificar fatores associados à magnitude da relação entre habilidades sociais e suporte social. Foram consultadas as bases de dados Scielo, Lilacs, Medline, PsycNET e Web of Science, recuperando a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
0
1
0
8
Order By: Relevance
“…The support network generates the self-confidence and the self-perception of being cared for, esteemed, loved, appreciated, valued and belonging to a network of mutual care. Social support is a mediator of negative states, bequeaths to the individual positive feelings and contributes to the prevention, protection and promotion and maintenance of health and psychological well-being (Fasihi Harandi et al, 2017;Ximenes et al, 2019). In this study three types of Social Support were identified: professional support, emotional support and informational support, as well as two sources: books and online resources.…”
Section: Social Support: Experience and Relevance In Pandemic Timesmentioning
confidence: 89%
“…The support network generates the self-confidence and the self-perception of being cared for, esteemed, loved, appreciated, valued and belonging to a network of mutual care. Social support is a mediator of negative states, bequeaths to the individual positive feelings and contributes to the prevention, protection and promotion and maintenance of health and psychological well-being (Fasihi Harandi et al, 2017;Ximenes et al, 2019). In this study three types of Social Support were identified: professional support, emotional support and informational support, as well as two sources: books and online resources.…”
Section: Social Support: Experience and Relevance In Pandemic Timesmentioning
confidence: 89%
“…Estudos têm apresentado resultados sobre a relevância das habilidades sociais e sua relação com indicadores de desenvolvimento socioemocional e bem-estar de adolescentes (Ximenes, et al, 2019;Akelaitis & Lisinskiene, 2018;Pereira-Guizzo, et al, 2018;Silva, et al, 2018;Romero-Olivaa et al, 2017;Uzunian & Vi-talle, 2015;Lv & Takami, 2015;Holopainen, et al, 2012).…”
Section: Habilidades Sociais Na Adolescênciaunclassified
“…Futuramente, após a elaboração de seu manual de aplicação, este instrumento poderá ser usado no contexto clínico para intervenções tanto individuais como em grupo, visando identificar os déficits e as habilidades sociais mais desenvolvidas em cuidadores de idosos (Queluz et al, 2020). Conforme anteriormente exposto, trabalhar as habilidades sociais nesta população pode contribuir para a melhora no vínculo familiar e também a uma maior disponibilidade de apoio para quem exerce o papel de cuidador principal, levando a uma melhor qualidade de vida de toda a família (Pinto et al, 2016;Ximenes, Queluz, & Barham, 2019).…”
Section: Precisãounclassified